Charting the future of PLOS Medicine: priorities for evidence, impact, and equity - Lumbard, Helen; Bärnighausen, Till (PLoS medicine, 2025)
As PLOS Medicine enters a new chapter, its leadership sets out a bold editorial vision grounded in evidence, impact and equity. In a rapidly evolving global health landscape, the journal reaffirms its commitment to diversity, openness, and actionable science, ensuring research not only reflects the world’s needs, but drives meaningful change.
Gesehen am 27.11.2025